Digital Transformation Through Management Information Systems: Opportunities and Challenges for Islamic Value-Based Organizations - Dwi Tika Wulan Sari; M. Romiz Assiddiqi; Sulistiya Puji Astuti; M. Rafi Fayyadh; Lia Fatra Nur Laili Kamalin; M. Reza Fahrezi; Ummu Kholil Prawesti; Diana Kristi; Adellia Saniyatuz Zahro; Rohadatul Marsa; Mansur Chadi Mursid (Idarotuna : Journal of Administrative Science, 2026)
Digital transformation has become a strategic necessity for modern organizations, including Islamic value-based organizations that are required to remain adaptive without abandoning sharia principles. This study aims to analyze the role of Management Information Systems (MIS) in digital transformation, identify opportunities and challenges for their implementation, explore patterns of Islamic value integration, and formulate a contextual MIS adoption model. The method used is a qualitative approach through literature studies using content analysis and thematic analysis techniques of various scientific sources and institutional reports. The results show that MIS plays a key role in improving operational efficiency, the quality of data-driven decision-making, and organizational transparency. MIS implementation opens up opportunities for increased innovation, efficiency, and accountability, but is faced with challenges such as cultural resistance, limited digital literacy, and gaps in the integration of Islamic values ​​that are still symbolic. Therefore, an integrative approach is needed through holistic, contextual, and cultural patterns so that Islamic values ​​are substantively internalized in the system. This study produces a value-based MIS adoption model that emphasizes the balance between technological readiness, organization, and the principles of maqasid al-shariah. The implications of this research provide a conceptual contribution in developing a digital transformation framework based on Islamic values ​​that is adaptive, ethical, and sustainable.